Preconception fear of childbirth: experiences and needs of women fearing childbirth before first pregnancy - Elisabet Rondung; Susanna Magnusson; Elin Ternström (BMC, 2022)
Plain English summary: Many researchers have studied the experiences of pregnant women who are afraid of giving birth. Although it is known that women can fear childbirth long before becoming pregnant, little research has investigated this issue. In this study, we interviewed nine women who wanted to have children but did not dare become pregnant because they were afraid of giving birth. The women perceived childbirth as an extremely risky event and doubted their abilities to cope with it. They tried to cope with their fear by seeking information about pregnancy and childbirth. They also tried not to think about these issues and did what they could to avoid becoming pregnant. The women felt abandoned as they had to deal with their fear on their own. They wanted support from maternal care services, but this was seldom the case. Instead, they felt pressured to decide whether to dare become pregnant or not without support. Here, we want to give voice to the experiences of this often-neglected group of women and make researchers, policy makers, and health care personnel aware of the needs of women who are afraid of giving birth before becoming pregnant. We encourage maternal care services to consider how they can support these women.